Site‐Selective Catalysis of a Multifunctional Linear Molecule: The Steric Hindrance of Metal–Organic Framework Channels - Zhang, Weina (2018)
The site‐selective reaction of a multifunctional linear molecule requires a suitable catalyst possessing both uniform narrow channel to limit the molecule rotation and a designed active site in the channel. Recently, nanoparticles (NPs) were incorporated in metal–organic frameworks (MOFs) with the tailorable porosity and ordered nanochannel, which makes these materials (NPs/MOFs) highly promising candidates as catalytic nanoreactors in the field of heterogeneous catalysis. Inspired by a “Gondola” sailing in narrow “Venetian Canal” without sufficient space for a U‐turn, a simple heterogeneous catalyst based on NPs/MOFs is developed that exhibits site‐selectivity for the oxidation of diols by restricting the random rotation of the molecule (the “Gondola”) in the limited space of the MOF channel (the narrow “Venetian Canal”), thereby protecting the middle functional group via steric hindrance. This strategy is not limited to the oxidation of diols, but can be extended to the site‐selective reaction of many similar multifunctional linear molecules, such as the reduction of alkadienes.